Analysis of excimer laser treatment outcomes and corresponding angle κ in hyperopic astigmatism. Issue 7 (July 2019) - Frings, Andreas; Druchkiv, Vasyl; Pose, Lumi; Linke, Stephan J.; Steinberg, Johannes; Katz, Toam
Abstract : Purpose : To investigate the prevalence of preoperative, intraoperative, and postoperative angle κ in hyperopic eyes and its effect on the refractive outcomes of excimer laser vision correction. Setting : University Hospital Hamburg and Care Vision Refractive Centers, Germany. Design : Retrospective multicenter study. Methods : Hyperopic patients after laser in situ keratomileusis and before retreatment because of hyperopic regression were included. Three treatment groups were defined based on the magnitude of preoperative angle κ defined as low (<0.25 mm), moderate (0.25 to 0.50 mm), or high (>0.50 mm). Results : The study analyzed 170 hyperopic eyes of 112 patients (mean age 29.8 years ± 10.04 [SD], range 21 to 62 years). The preoperative angle κ was low, moderate, or high in 23, 49, and 98 cases, respectively. In eyes with a preoperative angle κ of 0.25 mm or more, changes in the x ‐axes and y ‐axes of angle κ and its magnitude were statistically significant ( P < .05) between preoperative and intraoperative measurements. In these eyes, intraoperative angle κ (offset) was statistically significantly smaller ( P < .05), and Purkinje images were statistically significantly more caudal ( P < .001). Treatment predictability was independent from using preoperative or intraoperative angle κ, and there were no statistically significant differences in efficacy or safety. Conclusions : A preoperative magnitude of angle κ as high as 0.50 mm or higher was present in more than 50% of regressed hyperopic eyes. Measuring angle κ preoperatively did not reflect its real‐time intraoperative magnitude. Using the preoperatively larger angle κ as an intraoperative offset might result in a too nasally centered ablation that causes topographic and optical drawbacks; therefore, centering the ablation based on the intraoperative measured offset is recommended.